2019
DOI: 10.21608/smj.2019.41384
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Anxiety, Depression, and Problematic Internet Use among a Sample of university students in Egypt

Abstract: Objective:Problematic Internet Use (PIU) is a growing problem among adolescents. This study was designed to investigate the prevalence of PIU and to explore the relationship between anxiety, depression ,and PIU among sample of Egyptian university students. Methods:A cross-sectional survey was conducted from February 2017 to January 2018on a random sample of 588 students selected from four faculties in Sohag University. PIU was assessed by the 20-item Young Internet Addiction Test (YIAT). Information was also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…To examine the association of internet addiction with sex, 14 studies were included (Kamal and Mosallem, 2013 ; Alhajjar, 2014 ; Shaheen and Farahat, 2016 ; Effat et al, 2019 ; Arafa et al, 2020 ; Boudabous et al, 2020 ; Ebrahim Essa and Elsherif, 2020 ; Mboya et al, 2020 ; Salama, 2020 ; Zenebe et al, 2020 ; Abd El-Mawgood et al, 2021 ; Ilesanmi et al, 2021 ; Omoyemiju and Popoola, 2021 ; Study and Mengistu, 2021 ). Among these, 10 studies reported a significantly higher odds of internet addiction among male adolescents (Alhajjar, 2014 ; Shaheen and Farahat, 2016 ; Effat et al, 2019 ; Arafa et al, 2020 ; Boudabous et al, 2020 ; Ebrahim Essa and Elsherif, 2020 ; Salama, 2020 ; Ilesanmi et al, 2021 ; Omoyemiju and Popoola, 2021 ; Study and Mengistu, 2021 ). The pooled estimate showed a significant association between sex and internet addiction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the association of internet addiction with sex, 14 studies were included (Kamal and Mosallem, 2013 ; Alhajjar, 2014 ; Shaheen and Farahat, 2016 ; Effat et al, 2019 ; Arafa et al, 2020 ; Boudabous et al, 2020 ; Ebrahim Essa and Elsherif, 2020 ; Mboya et al, 2020 ; Salama, 2020 ; Zenebe et al, 2020 ; Abd El-Mawgood et al, 2021 ; Ilesanmi et al, 2021 ; Omoyemiju and Popoola, 2021 ; Study and Mengistu, 2021 ). Among these, 10 studies reported a significantly higher odds of internet addiction among male adolescents (Alhajjar, 2014 ; Shaheen and Farahat, 2016 ; Effat et al, 2019 ; Arafa et al, 2020 ; Boudabous et al, 2020 ; Ebrahim Essa and Elsherif, 2020 ; Salama, 2020 ; Ilesanmi et al, 2021 ; Omoyemiju and Popoola, 2021 ; Study and Mengistu, 2021 ). The pooled estimate showed a significant association between sex and internet addiction.…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis of five studies (Shaheen and Farahat, 2016 ; Effat et al, 2019 ; Ebrahim Essa and Elsherif, 2020 ; Salama, 2020 ; Abd El-Mawgood et al, 2021 ), adolescents that reside in urban areas are 2 times more likely to have internet addiction as compared to those who reside in rural areas (POR = 2.32, 95% CI:1.19–4.53). Moderate heterogeneity was observed in the random-effects model (I 2 = 59.39%, P -value = 0.08) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a prevalence rate of 58.0 % for depression symptoms among Egyptian youth with a mean age of 20.18 ± 1.50 years [ 8 ], using 5% accepted degree of precision, α of 0.05 and power of 95%, the minimum required sample size was 375 participants. The sample size increased up to 447 participants.…”
Section: Methodsmentioning
confidence: 99%
“…[ 3 ] In the previous studies from the Middle East and Asia, the prevalence of internet addiction among adolescent and university students varies from 0.9% to as high as 33%. [ 4 5 6 7 8 9 10 11 ] Previous study in Saudi Arabia found that 1.9%–3.1% of medical students were classified as internet addicted. [ 12 13 ] This study aimed to determine the prevalence of internet addiction and its associated factors among medical students at Taibah University in Madinah, KSA.…”
Section: Introductionmentioning
confidence: 99%